MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU LULUSAN DI MAN SE-KOTA BANDAR LAMPUNG - Gunawan, Reski; Yetri, Yetri; Fauzan, Ahmad (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the implementation of Human Resource Management (HRM) in improving graduate quality at Islamic Senior High Schools (MAN) in Bandar Lampung City by examining seven key HRM functions, namely human resource planning, recruitment and selection, training and professional development, performance evaluation, career development, teacher motivation and welfare, and Islamic work culture. This research employed a qualitative approach with a descriptive case study design, in which data were collected through in-depth interviews, observations, and document analysis, and were analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that human resource planning is carried out through teacher needs analysis and workload mapping, enabling more appropriate teacher placement in accordance with curricular demands. Recruitment and selection are implemented rigorously through microteaching and structured interviews to ensure compatibility between teacher competencies and institutional values. Training and professional development are conducted continuously through workshops, MGMP programs, and internal mentoring, which significantly strengthen teachers’ pedagogical competencies. Performance evaluation functions as a basis for professional coaching, while career development motivates teachers to enhance their professionalism. Moreover, teacher motivation is shaped by recognition, a religious work atmosphere, and harmonious interpersonal relationships, whereas Islamic work culture supports character building and the creation of a positive learning environment. Overall, this study concludes that the integrated implementation of HRM functions significantly contributes to improving the quality of graduates at MAN schools in Bandar Lampung City.